2008
DOI: 10.1097/brs.0b013e318160462a
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Gender Differences in Cervical Vertebrae of Size-Matched Volunteers

Abstract: Present results of decreased linear and areal cervical dimensions leading to decreased column stability may partially explain increased traumatic injury rates in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 31 publications
3
45
0
1
Order By: Relevance
“…Dimensional measurements match with literature. 16 Histological examination showed cervical spinal segment's intervertebral disc with a gray, inhomogeneous structure with unclear distinction between the nucleus and annulus. These were classified to have grade III degeneration.…”
Section: Resultsmentioning
confidence: 99%
“…Dimensional measurements match with literature. 16 Histological examination showed cervical spinal segment's intervertebral disc with a gray, inhomogeneous structure with unclear distinction between the nucleus and annulus. These were classified to have grade III degeneration.…”
Section: Resultsmentioning
confidence: 99%
“…This may contribute to decreased stability of the cervical column and an increased risk of injury in females. Republished with permission from Stemper et al 94 Copyright ©2008 Wolters Kluwer Health, Inc. to a variability in outcomes sufficient to partially explain the analytical finding that underlying mechanical factors, such as collision severity, have no predictive value for patient outcomes across a large sample of patients, 111 while experimental vical spine, increasing soft tissue strains in structures associated with whiplash injury. 6,21,65,91 As shown here, morphological differences among occupants can have a significant effect on cervical spine biomechanics and may contribute Likewise, Curry and colleagues 17 identified onset of end-plate failures with segmental prealignment and cortical fracture with lordotic curvature during axial loading.…”
Section: Cervical Spinal Posturementioning
confidence: 99%
“…This may contribute to decreased stability of the cervical column and an increased risk of injury in females. Republished with permission from Stemper et al 94 Copyright ©2008 Wolters Kluwer Health, Inc. The clinical association of cervical spine curvature with patient outcomes is less clear.…”
mentioning
confidence: 99%
“…Chatzigianni and Halazonetis, 6 using lateral cephalograms, reported that gender dimorphism was found for both cervical vertebral size and shape. Hellsing 22 and Stemper et al 23 also found gender differences in vertebral size. However, we found no gender differences in CS.…”
Section: Discussionmentioning
confidence: 99%
“…This might produce differences compared with previous studies. 6,[22][23][24] Through GPA and PCA, we found meaningful PCs (Table 1); the first three PCs in the vertebral foramen for ACV1 and two PCs in the vertebral body for the ACV3 and ACV4. Figure 3 shows the mean shape.…”
Section: Discussionmentioning
confidence: 99%